2022
DOI: 10.1021/acs.jpclett.2c01399
|View full text |Cite
|
Sign up to set email alerts
|

PEDOT:PSS/CuCl Composite Hole Transporting Layer for Enhancing the Performance of 2D Ruddlesden–Popper Perovskite Solar Cells

Abstract: Poly­(3,4-ethylenedioxythiophene):polystyrenesulfonate (PEDOT:PSS) is a popular hole transport layer (HTL) in 2D Ruddlesden–Popper (RP) perovskite solar cell (PSCs) due to its highly conductive, transparent, and solution-processable characteristics. However, fundamental questions such as its strong acidity or mismatched energy level with the 2D RP photoactive layer often restrict the performance and stability of devices. Herein, copper chloride (CuCl), a common direct band gap semiconductor, is doped into PEDO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…Previous study has demonstrated that the (111) planes are almost perpendicularly oriented and (202) planes are perfectly perpendicularly oriented. Thus, the lower ratio of (111) and (202) indicates a high degree of vertical orientation, which is beneficial for charge transport. , In order to more clearly verify the influence of 4-HP, we further increase the doping concentration of 4-HP in BA 2 MA 3 Pb 4 I 13 films up to 10% mol (Figure j). We found that the (111)/(202) intensity ratio decreases more obviously, certifying the key role of 4-HP in changing the crystal orientation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous study has demonstrated that the (111) planes are almost perpendicularly oriented and (202) planes are perfectly perpendicularly oriented. Thus, the lower ratio of (111) and (202) indicates a high degree of vertical orientation, which is beneficial for charge transport. , In order to more clearly verify the influence of 4-HP, we further increase the doping concentration of 4-HP in BA 2 MA 3 Pb 4 I 13 films up to 10% mol (Figure j). We found that the (111)/(202) intensity ratio decreases more obviously, certifying the key role of 4-HP in changing the crystal orientation.…”
Section: Resultsmentioning
confidence: 99%
“…The device with the introduction of 4-HP can significantly increase the recombination resistance ( R rec ) to 12 kΩ, implying improved charge transfer capacity and carrier recombination. To further validate the effectiveness of the 4-HP additive on passivating defects, defect density ( N Trap ) was quantified using the space charge-limited current (SCLC) method through the device architecture of ITO/PEDOT:PSS/PVK/MoO 3 /Cu (Figure d), according to the formula , N Trap = 2 ε ε 0 V TFL q L 2 where V TFL is the onset voltage of the trap-filled limit region, ε 0 is the vacuum permittivity, ε is the relative dielectric constant, q is the elementary charge, and L is the film thickness . The N Trap values of the 4-HP-doped BA 2 MA 3 Pb 4 I 13 films were figured out to be 6.23 × 10 15 and 3.96 × 10 15 cm –3 based on the values of V TFL , implying that the doping of 4-HP is capable of reducing the nonradiative recombination in the 4-HP-doped devices.…”
Section: Resultsmentioning
confidence: 99%
“…Commercial products needed a balance between water stability and optoelectronic performance to explore optimal conditions for target applications. It has been demonstrated that adding conductive conjugated polymers 147,148 (such as PEDOT 149 and P3HT 150 ) increases stability, passivates surfaces, and increases intrinsic conductivity. Future research can concentrate on the synthesis of conducting polymer-coated perovskite NCs to enhance the transport characteristics in the films which is rarely explored.…”
Section: Discussionmentioning
confidence: 99%
“…[19] It is believed that the dominant reason for the lower PCE of the PEDOT:PSS-based devices compared to the PTAA-based devices is the large V oc loss due to the energy level mismatch between the perovskite layer and PEDOT:PSS. [20][21][22][23][24][25][26][27][28][29] The energy level of PEDOT:PSS ranges from −4.9 to −5.1 eV, which is much higher than the valence band maximum of perovskite (−5.4 eV for MAPbI 3 ). [30] In addition, it is reported that methylammonium iodide (MAI) could react with PEDOT:PSS, leading to V oc loss in the PSCs based on PEDOT:PSS.…”
Section: Introductionmentioning
confidence: 99%